An Empirical Analysis Of The Determinants Of Exchange Rate In Nigeria - Ojo., Oke, Michale; Temitayo, Adetan, Taiwo (International Journal of Scientific Research and Management (IJSRM), 2018)
This study examined empirically the determinants of exchange rate in Nigeria using the ARDL Bounds test approach to co-integration for the period spanning 1986-2016. The result of the analysis shows that the gross domestic product (GDP), Interest rate (INT) and inflation rate (INF) have positive effect on exchange rate in Nigeria while degree of openness (DOP) recorded a negative effect on exchange rate (EXR) in Nigeria. The Error Correction Mechanism result appeared to be correctly signed and significant. The study therefore concluded that gross domestic product, interest rate and inflation rate are the major determinant of exchange rate in Nigeria under the study period. It is therefore recommended that government should focus more on production of goods and services that can be exported and also introduce policies that can discourage importation of goods into the country. The government must pursue a realistic and pragmatic exchange rate policy in  the  less  free  trade areas that would stem capital  flight and  ensure more investment in the Nigerian economy.